The Study of Difference Piping Wall Thickness Against the Difference Pressure Applied at UTHM Biodiesel Plant Using Simulation Method - Muhammad Khairul Haziq Marzuki,; Bachik Abu Bakar,; Norrizal Mustaffa, (Progress in Engineering Application and Technology, 2022)
The study is concerned about the withstand of the piping system at the Universiti Tun Hussein Onn (UTHM) Biodiesel Plant during operation using different pipe thicknesses against the variation of applied pressure. The range of the wall thickness used is 2.77mm, 3.91mm, and 5.54mm which follow the ASME B36.10 code and standard. Next, the piping selection characteristics are fully followed as actual at the UTHM biodiesel plant. The pipe material used is A53 B carbon steel pipe, actual dimension for length and height is at actual, the temperature design is 250oC, and the 8 to 12 bars operating pressure are applied. This study is performed using the Solid Works 2020 software simulation method. Two methods in simulations are being used which are Computational Fluid Dynamics (CFD) for flow simulation and Finite Element Analysis (FEA) to analyze the static pressure. The CFD is functioning to recognize the highest point of the part along with the piping system for the selected applied pressure. The selected pipe is being tested and measured using the FEA simulation to investigate the maximum value of stress and strain to withstand the applied pressure. From the analysis, the elbow pipe is the highest-pressure point located for flow distribution along with the piping system. The study shows that the 3.91mm wall thickness for the piping system that is used at the UTHM biodiesel plant is acceptable and comply with the ASME B36.10 code and standard. The result for the 2.77mm and 5.54mm wall thicknesses, it also acceptable but not economical in terms of safety and cost of the material.